PARTOCRACY AND CLIENTILISM IN BOSNIA AND HERZEGOVINA - Simovic, Vlade; Gajic, Drasko (Politeia, 2025)
Political parties in a large number of countries of the world, from being democratizers, have over time become oligarchically organized groups that subordinate institutions to themselves and the interests of their leaders, devaluing the democracy for which they declaratively advocate. This phenomenon is expressed in transitional states whose civil societies and economies have not reached a development level sufficient to resist the partocratization of institutions and the clientelistic relationship of political subjects and citizens. Such is Bosnia and Herzegovina, which, within the framework of the phenomenon of partocracy, as the subject of research in this paper, we analyze in the form of a case study. The specificity of Bosnia and Herzegovina is that its nationally conditioned party segmentation further strengthens the power of party oligarchies whose leaders also act as national leaders. With the mortgage of war, war profiteering, poorly implemented privatization, the Daytonian constitutionalism destroyed and devastated communities, partocracy and clientelism in Bosnia and Herzegovina have become a systemic phenomenon and an everyday occurrence. They are one of the main factors of its dysfunctionality and underdevelopment, which is reflected in the work of public institutions, the definition of development and social policies.
Keywords: Partocracy; clientelism; corruption; Bosnia and Herzegovina